Risk, coping and PTSD symptom trajectories in World Trade Center responders. (November 2016) - Feder, Adriana; Mota, Natalie; Salim, Ryan; Rodriguez, Janice; Singh, Ritika; Schaffer, Jamie; Schechter, Clyde B.; Cancelmo, Leo M.; Bromet, Evelyn J.; Katz, Craig L.; Reissman, Dori B.; Ozbay, Fatih; et al.
Abstract: Trajectories of disaster-related posttraumatic stress disorder (PTSD) symptoms are often heterogeneous, and associated with common and unique risk factors, yet little is known about potentially modifiable psychosocial characteristics associated with low-symptom and recovering trajectories in disaster responders. A total of 4487 rescue and recovery workers (1874 police and 2613 non-traditional responders) involved during and in the aftermath of the unprecedented World Trade Center (WTC) attacks, were assessed an average of 3, 6, 8, and 12 years post-9/11/2001. Among police responders, WTC-related PTSD symptoms were characterized by four trajectories, including no/low-symptom (76.1%), worsening (12.1%), improving (7.5%), and chronic (4.4%) trajectories. In non-traditional responders, a five-trajectory solution was optimal, with fewer responders in a no/low-symptom trajectory (55.5%), and the remainder in subtly worsening (19.3%), chronic (10.8%), improving (8.5%), and steeply worsening (5.9%) trajectories. Consistent factors associated with symptomatic PTSD trajectories across responder groups included Hispanic ethnicity, pre-9/11 psychiatric history, greater WTC exposure, greater medical illness burden, life stressors and post-9/11 traumas, and maladaptive coping (e.g., substance use, avoidance coping). Higher perceived preparedness, greater sense of purpose in life, and positive emotion-focused coping (e.g., positive reframing, acceptance) were negatively associated with symptomatic trajectories. Findings in this unique cohort indicate considerable heterogeneity in WTC-related PTSD symptom trajectories over 12 years post-9/11/2001, with lower rates of elevated PTSD symptoms in police than in non-traditional responders. They further provide a comprehensive risk prediction model of PTSD symptom trajectories, which can inform prevention, monitoring, and treatment efforts in WTC and other disaster responders.